2012
DOI: 10.1007/s12630-012-9696-6
|View full text |Cite|
|
Sign up to set email alerts
|

Influences observed on incidence and reporting of medication errors in anesthesia

Abstract: Background Medication errors are a common occurrence during the conduct of anesthesia (one in 113-450 patients). Several factors contribute to medication errors in anesthesia, including experience of the anesthesia provider, severity of comorbidities, and type of procedure. The inexperience of anesthesia providers-in-training also leads to increased error rates. This prospective observational study repeats and extends previous work by Webster et al. and Llewellyn et al. examining the role of comorbidities, typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 19 publications
3
96
2
1
Order By: Relevance
“…6 The focus of this current review is on strategies that are currently being engineered into care delivery systems to reduce drug-related errors in anesthetic practice. Such errors, which occur at a rate of about 1 per 130-450 patients, [7][8][9][10][11] are associated with increases in morbidity, mortality, and the costs of hospital care. [8][9][10][11][12] Fortunately, most anesthetic-related errors are inconsequential; however, some lead to substantial or permanent injury and even death.…”
Section: Résumémentioning
confidence: 99%
See 2 more Smart Citations
“…6 The focus of this current review is on strategies that are currently being engineered into care delivery systems to reduce drug-related errors in anesthetic practice. Such errors, which occur at a rate of about 1 per 130-450 patients, [7][8][9][10][11] are associated with increases in morbidity, mortality, and the costs of hospital care. [8][9][10][11][12] Fortunately, most anesthetic-related errors are inconsequential; however, some lead to substantial or permanent injury and even death.…”
Section: Résumémentioning
confidence: 99%
“…Based on a limited number of prospective studies, the estimated incidence of medication error in anesthetic practice ranges from 0.33-0.73%, 7,9 and the rate has not changed substantially in over 15 years. 11 Despite a growing awareness of the importance of drug safety, medication error is a major cause of medical malpractice for anesthesiologists in Canada.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation
“…18 Five reports from around the globe over the next 11 years reported similar results. [19][20][21][22][23] These large-scale studies, some retrospective and others prospective, relied on paperbased technology. While these paper-based systems did show opportunities for improvement, the resources involved with reviewing paper records and incident reports have taken over 30 years to establish a baseline from which to assess the effect of intervention strategies on the rate of medication errors in anesthesia.…”
Section: Advantages Of Ehrs and Aimsmentioning
confidence: 99%
“…15 Cooper et al suggested that a shift of organizational culture over the past decade that emphasizes safety rather than blame may have accounted for the increased rate of voluntary reporting of errors that were observed over previously published reports. 23 The establishment of non-threatening environments may encourage clinician ''buy-in'' to clinical solutions aimed at improving patient care. Buntin et al found that the ''human element'' is critical to health IT implementation.…”
Section: Barriers To Adoption and Implementation Of Ehrs And Aimsmentioning
confidence: 99%